2009
DOI: 10.1021/ma900767s
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Hybrid Nanotubes Composed of Block Copolymer and Gold Nanoparticles

Abstract: We demonstrate the facile fabrication of high aspect ratio nanotubes from responsive block copolymer, polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP), and in situ grown gold nanoparticles. PS-b-P2VP nanotubes are fabricated by template-assisted assembly by utilizing cylindrical pores of porous alumina membranes followed by its dissolution. Solvent annealing was employed to facilitate ordered phase separation of the block copolymer with in the nanotube structure, followed by in situ formation of gold nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…[34][35][36] The X-ray photoelectron spectroscopy measurement of the functionalized textile indicated that the grafting of the block copolymer on the surface of the textile was achieved via a very small number of 2-vinylpyridine monomer units, and most of the pyridyl groups on P2VP-b-PDMS copolymer remained unchanged during the grafting process, which preserved the pH-responsive property of P2VP (Supplementary Figure S1). CA measurements were first conducted in air to probe the responsive wettability of the functionalized textile surface by using water droplets with different pH (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] The X-ray photoelectron spectroscopy measurement of the functionalized textile indicated that the grafting of the block copolymer on the surface of the textile was achieved via a very small number of 2-vinylpyridine monomer units, and most of the pyridyl groups on P2VP-b-PDMS copolymer remained unchanged during the grafting process, which preserved the pH-responsive property of P2VP (Supplementary Figure S1). CA measurements were first conducted in air to probe the responsive wettability of the functionalized textile surface by using water droplets with different pH (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…As a weak polybase, P2VP has a pK a of about 3.6. 34 When in contact with a water droplet with a pH of 6.5, P2VP is therefore in the deprotonated state and exhibits a collapsed conformation due to the hydrophobic interaction between the deprotonated P2VP chains. On the other hand, the PDMS block has a desirably low glass transition temperature (Tg) of about À62 1C (according to the supplier), and it can be considered as a liquid-like polymer with high flexibility at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…As has been reported, owing to its pH-responsive property, P2VP can alter its wettability as well as its conformation by protonation and deprotonation of its pyridyl groups in response to pH changes,26, 28, 29 and thus the grafted BCP endows the core/shell-structured particles with a pH-responsive property. Dynamic light scattering (DLS) and zeta potential measurements were first employed to characterize the pH-responsive property of the as-prepared RMPs in water with different pH values.…”
mentioning
confidence: 83%
“…[6] For example, pH-responsive nanotubes composed of gold nanoparticles--polystyrene-block-poly(2-vinylpyridine) (PSb-P2VP), which were fabricated by template-assisted assembly with cylindrical porous alumina membranes followed by its dissolution, exhibited a reversible change in the plasmon resonance position which is extremely beneficial in microfluidics and biosensing. [7] Patterned nanomaterials with different structures have attracted much research attentions due to their unique properties and wide applications. Different nanostructures, such as wires, rods, tubes, particles, flowers made from polymeric, metals, ceramics, composites, etc.…”
Section: Introductionmentioning
confidence: 99%